1989
DOI: 10.1063/1.343411
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced carbon-related defects in p-type silicon

Abstract: The production and removal of carbon-related defects have been investigated in 1-MeV electron-irradiated boron-doped silicon solar cells using deep level transient spectroscopy (DLTS). In Czochralski (CZ) material, the interstitial carbon defect (hole trap at Ev+0.27 eV), CI, decays by thermal and charge injection processes. We find that irradiation by MeV electrons creates CI while simultaneously removing it through the minority-carrier injection process. Removal of CI correlates with significant growth in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In silicon, the recombination enhancement of migration was found to be characteristic for many single interstitial atoms formed as result of irradiation. These are silicon self‐interstitial (Si i ) , aluminum interstitial (Al i ) , boron interstitial (B i ) and carbon interstitial (C i ) .…”
Section: Introductionmentioning
confidence: 99%
“…In silicon, the recombination enhancement of migration was found to be characteristic for many single interstitial atoms formed as result of irradiation. These are silicon self‐interstitial (Si i ) , aluminum interstitial (Al i ) , boron interstitial (B i ) and carbon interstitial (C i ) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one may expect the formation of this complex as a result of the recom bination induced diffusion of C i [7]. The possibility that a comparatively low H035 peak observed immedi ately after irradiation cannot be excluded as belonging to some as yet unidentified defect [11].…”
Section: Semiconductor Structures Low Dimensional Systems and Quantmentioning
confidence: 99%
“…It is clear that, in this case, a simple method for processing the data is found to be unsuit able and a special procedure is required. It is exactly the complexity of analysis of the H035b that accounts for the relatively large spread in the parameters determined by different researchers [4,5,7]. The existence of such spread induces doubts about the cor rectness of the procedure for simultaneous determina tion of concentration of centers under study as reported in the mentioned publications.…”
Section: Semiconductor Structures Low Dimensional Systems and Quantmentioning
confidence: 99%
See 1 more Smart Citation
“…These two defects have been studied extensively with the donor level of the divacancy established as having an energy level of around E v + 0.20 eV [5][6] [7] and the carbon interstitial an energy level of E v + 0.27 eV [8] [9].…”
Section: Introductionmentioning
confidence: 99%